Chronopotentiometric Deposition of Polypyrrole on Mild Steel in Tartrate Medium for Corrosion Prevention - Singh, Sanjay; Karki, Nabin; Gupta, Dipak Kumar; Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2025)
This work discusses the polypyrrole (PPy) deposition on mild steel (MS) from 0.4 M pyrrole in 0.1 M sodium potassium tartrate (Na-K tartrate) by chronopotentiometrically and the corrosion-resistant behavior in acid media. The current densities of 1, 2, and 3 mAcm-2 were used for the electrodeposition of PPy on MS. When current density 2 mA cm-2 was applied, no induction period associated with metal dissolution was observed. This behavior showed that very little dissolution of the MS occurs as the current density applied is ≥2 mA cm-2. Thus, the obtained polypyrrole (PPy) coated MS surface was examined by optical and scanning electron microscopy (SEM) which showed uniform, compact and adherent PPy coatings. The elemental composition of the PPy coating film was established by energy-dispersive x-ray (EDX) analysis. The corrosion performance was investigated by using potentiodynamic polarization (PDP) in 0.1 N H2SO4. It revealed that PPy coating considerably reduced corrosion current density, with an inhibition efficiency of 90.44%. The coating also behaved as a mixed inhibitor.